117k views
2 votes
HELP ME FIND X AND Y: 2x = 4y + 6 and 3x - y = -1

2 Answers

11 votes

Answer:

x = -1 and y = -2

Explanation:

2x = 4y +6

x = 2y + 3

3(2y+3) - y = -1

6y+9 - y = -1

6y - y = -10

5y = -10

y = -2

2x = 4(-2) + 6

2x = -8 + 6

x = -4 + 3

x = -1

I hope this helps!

User James Martin
by
5.2k points
6 votes

Answer:

x = -1

y = -2

Explanation:

To get y by itself:

3x - y = -1

-y = -1 - 3x

y = 1 + 3x

Solve for x with substitution:

2x = 4(1 + 3x) + 6

2x = 4 + 12x + 6

2x = 10 + 12x

-10x = 10

x = -1

Plug the x value into 3x - y = -1

3(-1) - y = -1

-3 - y = -1

-y = 2

y = -2

User Veera
by
4.9k points